Time Lost in the Archives - Broncano, Fernando (2014)
The author analyze the trend, determined by the evolution of contemporary technologies, towards the consolidation of a culture that privileges the novelty and immediacy above the heritage, and that therefore replaces institutions of historical memory, such as archives, libraries and museums, for private practices of mass and compulsive storage centered on trivial or not discerned information. Besides, this paper research the epistemological, ethical and political issues involved in this rise of a technological culture which is compromised with an inmediatist orientation.